HRYHORIJ WERWES – WYBITNY UKRAIŃSKI POLONISTA DRUGIEJ POŁOWY XX WIEKU - Radyszewski, Rostysław (Prace Polonistyczne, 2022)
The article presents the multifaceted academic and research activity of Hryhoriy Werwes, an outstanding Slavist and Polish philologist of the latter half of the twentieth century, a promoter of science, a member of the Ukrainian National Academy of Sciences, the long-term head of the Slavic and Balkan Studies Department at the Taras Shevchenko Literature Institute of the Ukrainian National Academy of Sciences and a member of the International Association for the Research and Popularization of Slavic Cultures at the UNESCO. It offers a review of his most important works and monographs. Special attention is paid to Werwes’s contribution to Polish studies, including his works on such Polish authors as: Adam Mickiewicz, Julisz Słowacki, Władysław Orkan, and Jarosław Iwaszkiewicz. Additionally, the article examines Werwes’s comparative studies and his work towards fostering Polish-Ukrainian relations.